La configuración del teletrabajo por los órganos judiciales y la negociación colectiva: una mirada ilustrada - Megino Fernández, Diego (2024)
In the current and changing world of work, the intervention of courts of justice and collective bargaining is increasingly necessary. This is confirmed, for example, by the complex configuration of teleworking, a very important figure during the health pandemic caused by COVID-19 and called to have higher levels of prominence. This study, based on the most recent judicial decisions and collective agreements, aims to provide an exemplary and reflective overview of some of its main constituent elements. As you will have the opportunity to appreciate as you progress in the reading, although we should not underestimate the progress and efforts made to date from the social concertation, even today the courts must intervene too often and intensity to address the many edges and controversies raised. In fact, with few exceptions, many of the aspects under analysis have not yet crystallized in a relevant way in the conventional practice, thus confirming that teleworking requires a different and more ambitious treatment by the negotiating bodies.